Implemention Of Rahn Tasjily For The Benefit Of The Community Peureulak Pawnshop, East Aceh - Hoessien, Jalaluddin (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2026)
The requirements of society will dictate how economic practices develop. Efforts to create the Islamic economy revolve on the idea of maslahah. The central focus of this study is to analyze the current Islamic pawn system and its application of the notion of Rahn within the framework of Islamic law. Rahn, whose root meaning is "to hold," refers to the Islamic tradition of pledging a valued asset as security for a loan. This paper seeks to provide a thorough explanation of Rahn and examine its several applications in modern Islamic pawn institutions. In pawning, an object is pledged as security for a loan, with the understanding that if repayment becomes problematic, the collateral might be sold to cover the amount. One aspect of pawning is rahn tasjili, which is a moveable item that serves as collateral for debt. The rahin retains control over the collateral, which is used to pay off the loan, while the murtahin receives evidence of ownership. Staying safe, putting one's own needs first, and not engaging in acts that go against Islamic law, including usury, are the cornerstones of rahn tasjili. Research in the area was used in this effort. The methods used to gather data were documentation, interviews, and observation. Data reduction, presentation, verification, and collecting were all accomplished via the application of qualitative analytic methodologies